Rare taxa mediate microbial carbon and nutrient limitation in the rhizosphere and bulk soil under sugarcane–peanut intercropping systems - Fu, Yue; Tang, Xiumei; Sun, Tingting; Lin, Litao; Wu, Lixue; Zhang, Tian; Gong, Yifei; Li, Yuting; Wu, Haining; Xiong, Jun; Tang, Ronghua (Frontiers in Microbiology, 2024)
Microbial carbon (C) and nutrient limitation exert key influences on soil organic carbon (SOC) and nutrient cycling through enzyme production for C and nutrient acquisition. However, it remains unclear about the intercropping effects on microbial C and nutrient limitation and its driving factors between rhizosphere and bulk soil. Therefore, we conducted a field experiment that covered sugarcane-peanut intercropping, sole sugarcane, and peanut as controls, and to explore microbial C and nutrient limitation based on the vector analysis of enzyme stoichiometry; in addition, microbial diversity was investigated in rhizosphere and bulk soil. High throughput sequencing was used to analyze soil bacterial and fungal diversity through the 16S rRNA gene and ITS gene at a phylum level. Our results showed that sugarcane-peanut intercropping alleviated microbial C limitation in all soils, whereas enhanced microbial phosphorus (P) limitation solely in bulk soil. Microbial P limitation was also stronger in the rhizosphere than in bulk soil. These results revealed that sugarcane-peanut intercropping and rhizosphere promoted soil P decomposition and facilitated soil nutrient cycles. The Pearson correlation results showed that microbial C limitation was primarily correlated with fungal diversity and fungal rare taxa (Rozellomycota, Chyltridiomycota, and Calcarisporiellomycota) in rhizosphere soil, and was correlated with bacterial diversity and most rare taxa in bulk soil. Microbial P limitation was solely related to rare taxa (Patescibacteria and Glomeromycota) in rhizosphere soil, and related to microbial diversity and most rare taxa in bulk soil. The variation partitioning analysis further indicated that microbial C and P limitation was explained by rare taxa (7-35%) and the interactions of rare and abundant taxa (65-93%). This study indicated the different intercropping effects on microbial C and nutrient limitation in rhizosphere and bulk soil and emphasized the importance of microbial diversity, particularly rare taxa.